Mismatch Negativity as a Tool to Detect the Intensity Just Noticeable Difference - Busemnaz AVŞAR AKSU; Didem ŞAHİN CEYLAN; Gökçe GÜLTEKİN (Archives of Acoustics)
Mismatch negativity (MMN) essentially reflects auditory change detection. Although auditory change detection can potentially be assessed through behavioral auditory testing methods, the increased reliability of objective methods, such as MMN, makes them more valuable. The aim of this study was to detect and compare the intensity just noticeable difference using the MMN and a behavioral method. The level at which the intensity difference between the frequent stimulus and the infrequent stimulus was the lowest and the MMN wave elicited was accepted as the MMN threshold. A total of 60 subjects, 30 females (mean age 21.70, SD = 1.91 years) and 30 males (mean age 22.77, SD = 3.01), aged 20–30 years, were included in the study. In the whole sample, a significant difference was found between MMN thresholds obtained from the right ear side and MMN thresholds obtained from the left ear side, regardless of sex (p < 0.05). In the comparison of the values obtained using the behavioral method and MMN, no significant difference was found for either the right or the left side in both sexes (p > 0.05). The results showed that the values determined by the behavioral method and MMN on both the right and left ear sides were similar in both sexes.